PENGARUH TATA KELOLA PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MEDIASI - Kastelia Azaria; Muslichah Muslichah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
This study aims to examine the effect of corporate governance on firm value with earnings management as a mediating variable. The population of this study is all manufacturing companies in the basic and chemical industry sectors which were listed on the Indonesia Stock Exchange in the period of 2016-2018. The sampling technique used was purposive sampling method. The number of samples is 20 companies, if the period is three years, the number of observations is 60. Data analysis was performed using path analysis. The results of this study shows seven important findings. First, corporate governance that is proxied with managerial ownership has a negative effect on firm value. Second, corporate governance that is proxied with audit committee has a positive effect on firm value. Third, corporate governance that is proxied with managerial ownership has no effect on earnings management. Fourth, corporate governance that is proxied with audit committee have no effect on earnings management. Fifth, earnings management has a positive effect on firm value. Sixth, earnings management cannot mediate the effect of corporate governance which is proxy by managerial ownership on firm value. Seventh, earnings management cannot mediate the effect of corporate governance which is proxy by audit committee on firm value